Dynamics & Dimensions of Gender Inequality in India: A study on the dynamics and dimensions of gender inequality in India (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Gender inequality occurs at various dimensions and is the combined result of various socioeconomic, policy and cultural factors. The present study attempts to evaluate the trends of gender gap of India in the key dimensions such as education attainment, economic participation, health and political empowerment using data on Global Gender Gap Index of World Economic Forum for the sample period of 2006-2015. The global gender gap rank of India is 108 for the year 2015 among 145 countries. The global gender gap score and the score of all indicators has increased during the sample period. The gender inequality is very high in economic participation and political dimension in India. The gender inequality is very close to the global average in case of health and education. The positive and significant correlation was found between gender equality, economic growth and Human development Index of India.